UJI ANTIBAKTERI DAN FORMULASI SEDIAAN MASKER ANTI JERAWAT YANG MENGANDUNG KAYU MANIS (Cinnamomum burmanni Nees &T. Nees ) - Oom Komala; Ella Noorlaela; Andhika Dhiasmi (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2018)
Cinnamon contains eugenol and cinnamaldehyde compounds and is widely used as an anti acne. The aim of this research make cinnamon maskers which has antibacterial power of Staphylococus aureus, to know the effect of cinnamon maskers storage to quality, and  know Cinnamomum burmanii maskers prefered  by  panelist. Cinnamon extract is made by maceration method, Test the antibacterial activity of  maskers  by  diffusion  method. The evaluation of   maskers is done   stability test at  room temperature (25oC-30oC) and temperature 40oC for 8 weeks, and  test prefered  by panelists. Cinnamon  extract  maskers  is made with various concentrations of formula 1 with cinnamon extract 0%, formula 2 with 8% concentration, formula 3 with 10% concentration and formula 4 with 12% concentration, and  tetracycline is control. The results of  the study were known  maskers with  cinnamon 12% concentration  most effective as an antibacterial with average of 16 mm diameter and  most preferred, stable at  room  temperature  25oC-30oC  and  40oC for 8 weeks. pH of  Maskers ranges from 5.31 to 6.89 which is still the normal range for pH of the preparation. Key words: Pandan fragrance, Streptococcus mutans, mouthwash